An evaluation of relationship with polished stone value and skid resistance value based on a laboratory investigation - Preda Pichayapan (2019)
© 2019 Trans Tech Publications, Switzerland. Aggregates which are the main component of asphalt concrete play a major role in loading transfer and skid resistant performance of asphalt concrete. Therefore, reduction in friction resistance of aggregate would lead to a decrease in overall skid resistance of asphalt concrete which is a commonly used road pavement surface material. This research aims to evaluate relationship of aggregate friction capacity through the polished stone value and asphalt concrete skid resistance. In this study, a series of polished stone value tests on the study aggregate of limestone and sandy mudstone and British pendulum tests for skid resistance value of polished hot mix asphalt (HMA) slab. An accelerated polishing machine was used to create reduction of skid resistance of HMA slabs. Test results showed that reduction of polished stone value (PSV) of limestone 47.6% leads to a decrease of skid resistance value (SRV) approximately 43.8% of HMA slabs. Furthermore, 14.5% reduction of PSV of sandy mudstone causes a decrease of 20.3% SRV of HMA slabs. Finally, a relationship linear regression between PSV of aggregates and SRV of HMA slab was established.